Antibiotics and Probiotics in Animal Food Impact and Regulation - Ali Kamboh, Asghar (Veterinary Medicine and Science, 2023)
In many parts of the world, the use of antibiotics in food-producing animals is partially or completely banned. This has led to increased research to develop alternatives to antibiotic growth promoters (AGPs). Some of these alternatives include prebiotics, probiotics, and phytoadditives. This book focuses on probiotics, which are the most feasible option to replace AGPs because they directly modulate the gut microbiota and improve gut absorption, which ultimately accelerates growth and production. The book provides recent updates on the use of probiotics in farm animals including poultry, fish, and ruminants as well as pet animals.